Modelling of hydrological pathways in Irish cathchments - O'Brien, Ronan (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
Conceptually, the main hydrological pathways contributing to river discharge are overland flow, interflow, shallow groundwater and deep groundwater. The percentage of the river hydrograph derived from each of these pathways is an important aspect of any hydrological study and is the focus of this research. Data collected from four study catchments as part of this research (rainfall, river discharge and temperature data from the river and boreholes) and available data from supplementary catchments, were analysed to determine the contribution of the pathways to river discharge through the application of various analytical techniques. Physical separation methods (recharge coefficients, master recession curve analysis, digital filtering algorithms and temperature tracer analysis) were employed to provide realistic ranges for the percentage of the river discharge derived from each of the pathways utilising measured discharge in the river, the geological setting of the catchment and temperature measurements in the river and the subsurface into account.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin